A brief description designing, modelling, and materials of cam-follower mechanism. (2021) - Mishra, Ruby; Bhowmik, Diptanu
Abstract: The present demand for high-performance machinery requires the selection of materials and efficient methods for the design and fabrication of cam-follower. Many authors used various ways to modify the design, modelling, and performance of Cam-follower. The main objective of this paper is to study different materials, design optimization, modelling, and analysis of a camshaft. This study could be an essential step for fixing the materials and optimizing the size of the cam to avoid failure in the camshaft. Due to the high speeds rotation of the camshaft, it may cause stress and vibrations in the system. Therefore, instead of selecting conventional materials for Cam and follower mechanisms, this can be fabricated from Composite materials or Plastics. The self-lubricating composite Cam- Follower system requires no lubrication between the cam follower. Therefore, saving on grease and maintenance hence are the best choice for clean-room operations. Here the approach is mostly fixing composite materials for the cam model, and it's a static and dynamic analysis by using Computer-Aided Engineering. This research furnishes us possible to solve such situations as exact load values concerning other rotating members. The software package (SOLIDWORKS and ANSYS) tools have been formulated to amplify the researcher's learning process. The software packages produce careful data regarding the stress, strain, displacement, velocity rate, and frequency of vibration of the shaft.